Community-Driven Environmental Governance Transformation to Strengthen Legal Protection of Public Resource Management in Rural and Vulnerable Regions - Dedy Stansyah; Agatha Jumiatie; Patria B. Boneo (Green Social: International Journal of Law and Civil Affairs, 2024)
This study explores the effectiveness of community-driven governance in managing natural resources in post-conflict rural areas. The object of research focuses on governance models in the departments of Caquetá and Cesar, Colombia, where community-based initiatives have been implemented to address socio-environmental challenges. The main problem identified is the limited success of top-down regulatory approaches in promoting sustainability and legal compliance in these regions. The primary objective of the research is to assess the role of local participation in improving governance outcomes. To achieve this, the study employs a qualitative approach, using case studies and interviews to gather data from local stakeholders involved in natural resource management. The main findings suggest that community-driven governance models significantly enhance legal protection for public resources, fostering stronger compliance with environmental regulations and promoting sustainable practices. These models empower local communities, increase their engagement in decision-making, and improve the long-term management of resources. The research concludes that integrating community-driven approaches into national and regional legal frameworks is essential for achieving more effective and sustainable environmental governance. These findings contribute to the understanding of how governance can be adapted to better address the needs of vulnerable communities in post-conflict settings.